THE PROTECTION OF CULTURAL PROPERTY AND POST-CONFLICT KOSOVO - Serbenco, Eduard (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2005)
In the context of the unprecedented level of cultural destruction taking place in Kosovo since the international community took over in 1999, the author of this article seeks to provide an answer to two questions. First, whether the Serbian-built religious heritage in Kosovo deserves any international protection. Second, whether the two international authorities in place in Kosovo, UNMIK and KFOR, a NATO-led military force, are under any legal obligation to protect this religious heritage. Relying on the relevant international law provisions, the author determines that items of Serbian-built religious heritage in Kosovo qualify as cultural property of international value, thereby deserving international protection. Examining further the legal mandate received by the international administration in Kosovo, the author argues that both UNMIK and KFOR exercise public authority in this province, thus placing the Serbian religious heritage in question under their jurisdiction. As a result, the author concludes that the legal obligation to ensure the protection of cultural heritage in Kosovo, although normally assigned by international law to the territorial state, here devolves upon these two international entities.